Patient satisfaction and perceived service quality in hospitals: a systematic review of the literature - Matos, Maria Hespanha Garcia de (2021)
The shift in the overall scenery of the healthcare industry, its specificities and market pressures drove health organizations into considering service quality and patient satisfaction as vital strategies. As a consequence, patients became the centre of healthcare services and their inputs began to be gradually integrated in planning, evaluating and improving organizational processes and in supporting decision-making. The current work sought to review the literature on patient satisfaction and healthcare quality, specifically in the case of hospitals. A modified PRISMA framework was employed and an extensive search was conducted on the SCOPUS database. From the initial 1 442 references, 66 were included in the review. Time parameters were purposefully set at 1980, which corresponds to the publication of a cornerstone report. For a study to be selected it had to cover satisfaction or perceived quality from the patients’ viewpoint. From the analysis conducted, it was observed a spike on studies around the 2000’s; the majority of investigated countries are developing nations; the quantitative type and the SERVQUAL questionnaire were the most used methods; and most of the publications modified existing models. Furthermore, it is reported the dimensions that received the highest and lowest grades regarding expectations and perceptions, and also the extent of the attributes’ discrepancy. Additionally, numerous authors detected that expectation scores were markedly high. It was also noted that the expectation-perception gap and the overall service scores did not coincide in various occasions. Finally, patients regarded reliability as the most important dimension and tangibles as the least. Lastly, data on the influence of variables on quality perceptions and on satisfaction showed that while some effects are inconclusive others are consensual. Moreover, a broader analysis on how patients’ evaluations are affected suggests that the outcome measured might impact the variables’ effect. Lastly, several shortcomings of the review can be pinpointed: only considering one document type in the search, disregarding other forms of literature or evidence; the search being conducted in only one multidisciplinary database, SCOPUS; the weak dispersion of studies across contexts and locations, and the scarcity of data and details; not validating the core constructs of each paper; and findings having emerged from comparing studies employing distinctive procedures and from different settings.